Digital Nudges for Privacy Awareness: From consent to informed consent? - Bergram, Kristoffer; Gjerlufsen, Tony; Maingot, Paul; Bezençon, Valéry; Holzer, Adrian (AIS, 2020)
Maintaining a private life in our digital world is gradually becoming harder. With Internet services having ever increasing access to personal data, it is crucial to raise user awareness about what privacy guarantees they offer. Regulations have recently been enacted such as the European General Data Privacy Regulation (GDPR). Yet, online service providers still have terms and privacy policies to which users tend to agree without ever viewing or reading them. By using digital nudges, this paper explores how small changes in the choice architecture can be designed to increase the informed consent and privacy awareness of users. The results from a double-blind online experiment (n = 183) show that phrasing the agreement differently and providing a highlights alternative to the existing quick-join choice architecture can significantly increase the number of users who view and read the terms and privacy policy. However, these digital nudges seem to not increase the users’ recollection of what they have agreed to. The experimental results are complemented by a field test using one of the proposed designs in the IKEA Place app (n = 81’431).
Keywords: digital nudging; persuasive technology; online privacy; choice architecture; design features; HCI; privacy policy; terms and conditions; privacy awareness; informed consent; biggest lie on the Internet